Tolerance of Listeria monocytogenes to biocides used in food processing environments. (August 2021) - Duze, Sanelisiwe Thinasonke; Marimani, Musa; Patel, Mrudula
Abstract: Listeria monocytogenes is a foodborne pathogen that causes a life-threatening disease in humans known as listeriosis. Contamination of food during processing is the main route of transmission of Listeria monocytogenes. Therefore, biocides play a crucial role in food processing environments as they act as the first line of defense in the prevention and control of L. monocytogenes . Residues of biocides may be present at sublethal concentrations after disinfection. This, unfortunately, subjects L. monocytogenes to selection pressure, giving rise to tolerant strains, which pose a threat to food safety and public health. This review will give a brief description of L. monocytogenes, the clinical manifestation, treatment of listeriosis as well as recently recorded outbreaks. The article will then discuss the current literature on the ability of L. monocytogenes strains to tolerate biocides especially quaternary ammonium compounds as well as the mechanisms of tolerance towards biocides including the activation of efflux pump systems. Highlights: Extensive disinfectant use can give rise to tolerant strains in L. monocytogenes . It can occur due to VBNC state, cell surface modification and biofilm formation. It can also be due to genotypic changes rather than a short phenotypic adaptation. Chromosome and plasmid mediated efflux pump genes can confer tolerance. Tolerance to quaternary ammonium compounds may select for antibiotic resistance.